Ab-3=cb-2d

Simple and best practice solution for Ab-3=cb-2d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Ab-3=cb-2d equation:


Simplifying
Ab + -3 = cb + -2d

Reorder the terms:
-3 + bA = cb + -2d

Solving
-3 + bA = bc + -2d

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1bc' to each side of the equation.
-3 + bA + -1bc = bc + -1bc + -2d

Combine like terms: bc + -1bc = 0
-3 + bA + -1bc = 0 + -2d
-3 + bA + -1bc = -2d

Add '3' to each side of the equation.
-3 + bA + 3 + -1bc = 3 + -2d

Reorder the terms:
-3 + 3 + bA + -1bc = 3 + -2d

Combine like terms: -3 + 3 = 0
0 + bA + -1bc = 3 + -2d
bA + -1bc = 3 + -2d

Reorder the terms:
-3 + bA + -1bc + 2d = 3 + -2d + -3 + 2d

Reorder the terms:
-3 + bA + -1bc + 2d = 3 + -3 + -2d + 2d

Combine like terms: 3 + -3 = 0
-3 + bA + -1bc + 2d = 0 + -2d + 2d
-3 + bA + -1bc + 2d = -2d + 2d

Combine like terms: -2d + 2d = 0
-3 + bA + -1bc + 2d = 0

The solution to this equation could not be determined.

See similar equations:

| (-2y+8)+2y=8 | | -2+5x=7(x+1)+1 | | 51+y=67 | | b-6=14 | | 6(n-5)-7n=5+4n | | 5x-6=18+2x | | .5x-y=18 | | 14x-20=4x | | 1-6r=-10+5r-6-5 | | 2y+5x=-7 | | 29x+14-17x=62 | | 12a+19b+6c+2c-5b-4a= | | 3(-5b+1)=b+35 | | -x=-6-3y | | 1-4b=11-6b | | An=5n-6 | | 2y-9=18-6x | | x+y-3z=8 | | -3x-10=-16 | | 5x+2y=-7 | | 5x+40*4x-24=0 | | 18p+11q+p-4q-4p= | | -1+6+6n-6n=4n-5n | | 3w^3=27w | | s-49=-29 | | 33-3x=8-8x | | 4x+9=-39-4x | | 9m+3n-2m+7n= | | -3x+4-6x-2=-13 | | -10-7x=-2y | | -81=-3x+6(6x+3) | | 6+0.10x=0 |

Equations solver categories